The social well-being of second-generation Turks in two Austrian cities - Schnell, Philipp (Migration Letters, 2014)
The most recent Austrian Integration Report indicates that a substantial proportion of Turkish immigrants do not feel at home in Austria. Whether these lower levels of social well-being also apply to the Turkish first, second or follow-up generations in Austria is uncertain. This article aims to fill this gap by asking how the Turkish second generation perceives their social inclusion into Austrian society. Results based on the TIES survey reveal that social well-being is largely determined by immigrants’ socio-economic achievements as well as by experiences of discrimination in their educational and occupational trajectories and daily life. Intergenerational progress is also found to be positively related with social well-being but at a much lower level.